Hydrogen peroxide centrally attenuates hyperosmolarity-induced thirst and natriuresis - Zanella, Regis C. [UNESP]; Melo, Mariana Rosso [UNESP]; Furuya, Werner Issao [UNESP]; Colombari, Eduardo [UNESP]; Menani, José V. [UNESP]; Colombari, Débora Simões Almeida [UNESP] (Elsevier B. V., 2016)
Intragastric hypertonic NaCl that simulates the ingestion of osmotically active substances by food intake induces thirst, vasopressin and oxytocin release, diuresis and natriuresis. Reactive oxygen species (ROS) produced endogenously in central areas may act modulating autonomic and behavioral responses. In the present study, we investigated the effects of H2O2 injected centrally on water intake and renal responses induced by increasing plasma osmolality with intragastric (ig) administration of 2M NaCl (2ml/rat). Male Holtzman rats (280-320g) with stainless steel cannula implanted in the lateral ventricle (LV) were used. Injections of H2O2 (2.5μmol/1μl) into the LV reduced ig 2M NaCl-induced water intake (3.1±0.7, vs. PBS: 8.6±1.0ml/60min, p < 0.05), natriuresis (769±93, vs. PBS: 1158±168μEq/120min, p<0.05) and diuresis (4.1±0.5, vs. PBS: 5.0±0.5ml/120min, p<0.05). Injections of H2O2 into the LV also decreased meal associated water intake (4.9±1.5, vs. PBS: 11.0±1.7ml/120min). However, H2O2 into the LV did not modify 2% sucrose intake (3.3±1.5, vs. PBS: 5.4±2.3ml/120min) or 24h food deprivation-induced food intake (8.2±2.0, vs. PBS: 11.0±1.6g/120min), suggesting that this treatment does not produce nonspecific inhibition of ingestive behaviors. The data suggest an inhibitory role for H2O2 acting centrally on thirst and natriuresis induced by hyperosmolarity and on meal-associated thirst.
Keywords: Hypertonic saline; Osmoreceptors; Reactive oxygen species; Renal excretion; Water intake